Computer graphics - Barker, Adrian; Halliday, Eric (North Ryde, NSW. : Australian Film Television & Radio School, 1982)
The program diccusses and demonstrates computer graphic
Copy available in DVD format
Executive producer, Eric Halliday
Interview, Mike Minehan
Keywords: Computer graphics